Analysis of The Need for The Development of Ethnomathematics-Based Teaching Materials for Junior High School Students - Chasanah, Aprilia Nurul; Wicaksono, Arief Budi; Rahmawati, Fadhilah; Pamungkas, Megita Dwi; Franita, Yesi; Hendrastuti, Zuida Ratih; Gunawan, Gunawan (AlphaMath : Journal of Mathematics Education, 2024)
This research aims to analyze the ethnomathematics-based mathematics teaching materials for junior high school students. This analytical research uses a descriptive qualitative method. The subjects are junior high school mathematics teachers and students in Magelang. The objects include teachers’ and students’ responses to teaching materials and the learning process. The data are collected using a questionnaire sheet, observations, and interviews. The data are analyzed using the Miles-Huberman Interactive Analysis, which consists of data reduction, presentation, and conclusion. The results show that (1) teaching materials are available for the learning process; (2) teaching materials often used are textbooks and videos; (3) all teaching materials follow core (KI) and essential competencies (KD); (4) the students find it challenging to understand the materials contained in the available teaching materials; (5)the teaching materials need to be improved by providing concrete examples; (6) ethnomathematics-based learning models have not been implemented optimally, and; (7) the students agree to the development of ethnomathematics-based textbooks as the learning resources which makes them easier to understand the materials. The results of literature and field studies show that students need ethnomathematical-based teaching materials to improve their understanding. The cultural products that will be used in this research are the products of Magelang culture.